Influence of Switchgrass TDIF-like Genes on Arabidopsis Vascular Development - Tian, Dongdong; Tang, Jingwen; Luo, Liwen; Zhang, Zhe; Du, Kebing; Larkin, Robert M.; Shi, Xueping; Zheng, Bo (Frontiers in Plant Science, 2021)
As a member of the CLAVATA3 (CLV3)/EMBRYO SURROUNDING REGION (CLE) family, the dodecapeptide tracheary element differentiation inhibitory factor (TDIF) has a major impact on vascular development in plants. However, the influence of polymorphisms in the TDIF peptide motif on activity remains poorly understood. The model plant Arabidopsis provides a fast and effective tool for assaying the activity of TDIF homologs. We studied five TDIF homologs from a group of 93 CLE genes in switchgrass (Panicum virgatum), a perennial biomass crop, named PvTDIF-like (PvTDIFL) genes. The expression levels of PvTDIFL1, PvTDIFL3MR3 and PvTDIFL3MR2 were relatively high and all of them were expressed at the highest levels in the rachis of switchgrass. The precursor proteins for PvTDIFL1, PvTDIFL3MR3 and PvTDIFL3MR2 contained one, three, and two TDIFL motifs, respectively. Treatments with exogenous PvTDIFL peptides increased the number of stele cells in the hypocotyls of Arabidopsis seedlings, with the exception of PvTDIFL_4p. Heterologous expression of PvTDIFL1 in Arabidopsis strongly inhibited plant growth, increased cell division in the vascular tissue of the hypocotyl and disrupted the cellular organization of the hypocotyl. Although heterologous expression of PvTDIFL3MR3 and PvTDIFL3MR2 also affected plant growth and vascular development, PvTDIFL activity was not enhanced by the multiple TDIFL motifs encoded by PvTDIFL3MR3 and PvTDIFL3MR2. These data indicate that in general, PvTDIFLs are functionally similar to Arabidopsis TDIF but that the processing and activities of the PvTDIFL peptides are more complex.